ANALISIS OPTIMALISASI MANAJEMEN PERSEDIAAN PADA BAHAN BAKU BIJIH PLASTIK (DI PT. NISSEN CHEMITEC INDONESIA) - N. Neni Triana; Riza Muztaba; Muhamad Sayuti; Afif Hakim (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2021)
Material inventory as a very important thing for every company. Manufacturing companies generally have inventory to be able to provide the best service to customers. The purpose of this study is to try to achieve the minimum inventory levels possible, reduce storage costs, maximize material storage space for materials fast moving. The author uses ABC Analysis to determine the plastic ore material that is fast moving and is in class A. Then proceed with forecasting the needs of plastic ore raw materials for 2019. The Economic Order Quantity (EOQ) method is used in this study after knowing the material in class A with a percentage value of 64.20% of material requirements and to determine the quantity of inventory orders that minimize the direct cost of storing inventory, ordering costs and optimizing the frequency of ordering materials. This research is useful for companies by minimizing direct costs of inventory storage, ordering costs and optimizing the frequency of ordering materials. PT. Nissen Chemitec Indonesia usually orders material in 1 year, 12 times material orders, which means that every month the company will order materials. In this analysis, forecasting of material needs is carried out for September 2019 to December 2019 because from the January to August period the company has purchased material. Material purchase with a lead time of 14 days for all types of material. Before using the EOQ method, the total inventory cost of raw materials is Rp. 2,286,376.58 and the company does not have a safety stock. If using the EOQ method the total inventory cost of raw materials is Rp. 812,009 with a frequency of ordering 1 time in 4 months period. The safety stock is 1,095 kg, and the reorder point is if the raw material is at the amount of 2,618 kg. This research is expected to minimize procurement costs and optimize the number of purchases that can be used at PT. Nissen Chemitec Indonesia so that all raw material procurement processes can be better for the company.